Advantages Of Using Bio-Floc Technology In Feeding Artemia (Texas Journal of Multidisciplinary Studies, 2024)
The article provides information on the use of biofloc technology, its advantages and the results achieved when artificially feeding brine shrimp in the laboratory of the Department of Fisheries.